2023
DOI: 10.1136/bmjopen-2022-063969
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue outcomes following COVID-19: a systematic review and meta-analysis

Abstract: ObjectivesFatigue is a pervasive clinical symptom in coronaviruses and may continue beyond the acute phase, lasting for several months or years. This systematic review and meta-analysis aimed to incorporate the current evidence for postinfection fatigue among survivors of SARS-CoV-2 and investigate associated factors.MethodsEmbase, PsyINFO, Medline, CINAHL, CDSR, Open Grey, BioRxiv and MedRxiv were systematically searched from January 2019 to December 2021. Eligible records included all study designs in Englis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 230 publications
(469 reference statements)
0
5
0
1
Order By: Relevance
“…In addition, reduced exercise capacity as a result of critical illness hospitalisation is thought to contribute to reduced HRQoL and fatigue outcomes in recovered patients [ 91 ]. In a review examining predictors of fatigue, there was an inconsistent relationship between exercise capacity and fatigue outcomes in those who had more severe disease, with some studies finding a decrease in HRQoL despite improved exercise capacity [ 92 ]. A variety of common mental health outcomes, including post-traumatic stress disorder, anxiety and depression, were associated with fatigue 1 year post hospitalisation, although the pre-morbid burden of these was unknown.…”
Section: Long Covid and The Skeletal Musclesmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, reduced exercise capacity as a result of critical illness hospitalisation is thought to contribute to reduced HRQoL and fatigue outcomes in recovered patients [ 91 ]. In a review examining predictors of fatigue, there was an inconsistent relationship between exercise capacity and fatigue outcomes in those who had more severe disease, with some studies finding a decrease in HRQoL despite improved exercise capacity [ 92 ]. A variety of common mental health outcomes, including post-traumatic stress disorder, anxiety and depression, were associated with fatigue 1 year post hospitalisation, although the pre-morbid burden of these was unknown.…”
Section: Long Covid and The Skeletal Musclesmentioning
confidence: 99%
“…In addition, reduced exercise capacity as a result of critical illness hospitalisation is thought to contribute to reduced HRQoL and fatigue outcomes in recovered patients [91]. In a review examining predictors of fatigue, there was an inconsistent relationship between exercise capacity and fatigue outcomes in those who had more severe disease, with some studies finding a decrease in HRQoL despite improved exercise capacity [92].…”
Section: Skeletal Muscle and Fatiguementioning
confidence: 99%
“…Long term impacts after COVID-19-infection include multi-systemic problems, disabilities, and mental health problems, of which fatigue has emerged as the most reported symptom [ 17 19 ]. As many as almost half of all who have a history of probable or confirmed COVID 19-infection experience symptoms after recovery from infection [ 18 ], and about 40% of COVID-19 survivors experience fatigue three months after infection, with anxiety, depression and psychiatric comorbidity generating elevated risk [ 20 ]. We have previously shown in a cohort study that individuals with a history of probable or confirmed COVID-19 infection/infections are more likely to suffer from mental health problems, with post-COVID impairments and fatigue appearing as the main predictors of mental ill-health [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…The World Health Organization (WHO) COVID-19 Clinical Management: Living Guideline (30) highlights the importance of multidisciplinary, coordinated, person-centred, and safe rehabilitation with persons living with Long COVID (6,7,31,32). Specifically, physiotherapists (physical therapists), may help to mitigate disability and prevent symptoms associated with Long COVID such as dyspnea, fatigue, and pain, and guide workplace accommodations (7,17,(31)(32)(33)(34)(35)(36)(37)(38). It is critical for physiotherapists to screen for complications from COVID-19 before rehabilitation and on an ongoing basis, including PESE, cardiac impairment, exertional oxygen desaturation, and autonomic dysfunction.…”
Section: Total Manuscript Word Count: 6770 Introductionmentioning
confidence: 99%